Applying of the cross ratio to significant increase the watermark redundancy of a text image - Yawai, Wiyada; Hiransakolwong, Nualsawat (My University, 2012)
The objective of this experiment was to apply the cross ratio theory to significantly increase the watermark data redundancy and integrity verification performance of a multi-language text image. Here, the cross ratio of four collinear points was applied to control the watermark em-bedding and detection processes by using the intersection positions of the horizontal (H) and vertical (V) and double (H & V) grid lines which virtually run across the text-character skeleton lines as the guidelines. Three layers of grid-line intersections were tested using multi-language text images including Thai, English, Chinese and Arabic. Our experi-ments revealed that three layers of three patterns of grid-line intersec-tions on each multi-language text image page, in which these grid lines were drawn and used to create multiple layers of intersection points for embedding secret data bits for watermarking effectively yielded a huge watermark hiding-bit redundancy. Nevertheless, when all points are embedded, it would be helpful for owners to be able verify their integrity.
Keywords: Collinear points; Cross ratio; Integrity verification; Text image; Watermark hiding-bit redundancy